Neurolupus. Issue 1 (3rd February 2010) - Joseph, Fady G; Scolding, Neil J
Abstract : Systemic lupus erythematosus (SLE) is not an uncommon condition. Most neurologists are well aware that it can cause a wide range of neurological complications, and SLE almost invariably appears on 'differential diagnosis' lists in cases of clinical uncertainty. However, the precise nature of the manifestations of SLE in the central and peripheral nervous systems is perhaps less widely understood, and misperceptions about phenomenology and treatment are common. Here we survey some of the main primary neurological complications of SLE—'neurolupus'—while acknowledging that secondary problems, either iatrogenic or relating to other consequences of SLE (eg, hypertensive CNS disease, for example, secondary to renal lupus) are neither less serious nor less treatable.